UNDANG-UNDANG PUSAKA DALAM ISLAM : Suatu Kajian Perbandingan - Abdul Rashid Abdul Latiff (Al-Hidayah, 1987)
The Islamic inheritance system actually strengthens family ties and strengthens cooperation within the family from generation to generation. Strictly speaking, the Islamic inheritance system recognizes the rights of each heir in the inheritance in the widest possible way, opening up the possibility of inheriting to all heirs who are related by blood and marriage to the deceased, whether men, women, children, the elderly, people disabilities, even to babies still in the mother's womb. Therefore, it is clear that the system of property division brought by Islam essentially erodes every rule and custom of property division that violates the principle of division based on blood relations and marriage.